Pills, Injections, Rings, or Implants? PrEP Formulation Preferences of PrEP-Experienced African Women for HIV Prevention. (1st December 2021) - Ngure, Kenneth; Mugo, Nelly R.; Bukusi, Elizabeth A.; Kiptinness, Catherine; Oware, Kevin; Gakuo, Stephen; Musinguzi, Nicholas; Pyra, Maria; Garrison, Lindsey; Baeten, Jared M.; Haberer, Jessica E.
Abstract : Supplemental Digital Content is Available in the Text.